Pulmonary function of a paediatric cohort of patients with postinfectious bronchiolitis obliterans. A long term follow-up. Issue 2 (11th November 2014) - Colom, Alejandro J; Maffey, Alberto; Bournissen, Facundo Garcia; Teper, Alejandro
Abstract : Background: Postinfectious bronchiolitis obliterans (BO) is a chronic respiratory disease that usually follows a severe adenovirus infection. Objective: To determine the evolution of pulmonary function and clinical outcome of children with postinfectious BO during childhood. Methods: The study included patients diagnosed with postinfectious BO in whom at least two spirometries were performed within a minimum interval of 3 months. Results: 46 met the inclusion criteria. The mean (±SD) follow-up period was 12.5 (±3.5) years. 197 spirometries and 41 plethysmographies were performed. Initial (9±3 years old) lung function was as follows (z score, mean±SD): forced vital capacity (FVC) −3.8±1; forced expiratory volume in 1 s (FEV1 ) −4.4±1; FEV1 /FVC −2.2±1; forced expiratory flow (FEF)25–75 −3.7±1; total lung capacity (TLC) 120±26%; residual volume (RV) 309±108%; and RV/TLC 55±13. During childhood, FVC and FEV1 increased by a mean of 11%/year (95% CI 9.3% to 12.6%; p<0.0001) and 9%/year (95% CI 7.7% to 10.2%; p<0.0001), and the FEV1 /FVC ratio decreased by 1.9%/year (95% CI 1% to 2.8; p<0.001). The z score for FVC, FEV1 and FEV1 /FVC decreased by 0.07 z score/year (95% CI 0.1 to 0.01; p<0.05), 0.09 z score/year (95% CI 0.1 to 0.05; p<0.01) and 0.04 z score/year (95% CI 0.09 to 0.001; p<0.02), respectively. During the follow-up period, 69% of patients required at least one hospital readmission and five required mechanical ventilation. Nine patients developed a thoracic deformity, and seven whose bronchiectasis did not respond to clinical treatment underwent a lobectomy. Conclusions: After a 12 year follow-up period, pulmonary function remained severely impaired, showing an obstructive pattern with air trapping that slowly improved during childhood. An unequal growth of lung parenchyma over the airways suggests dysinaptic growth. Patients required frequent readmission due to recurrent respiratory infections, and hypoxaemia improved slowly over time.